Evaluation of proton inelastic reaction models in Geant4 for prompt gamma production during proton radiotherapy. (21st September 2015) - Jeyasugiththan, Jeyasingam; Peterson, Stephen W
Abstract: During proton beam radiotherapy, discrete secondary prompt gamma rays are induced by inelastic nuclear reactions between protons and nuclei in the human body. In recent years, the Geant4 Monte Carlo toolkit has played an important role in the development of a device for real time dose range verification purposes using prompt gamma radiation. Unfortunately the default physics models in Geant4 do not reliably replicate the measured prompt gamma emission. Determining a suitable physics model for low energy proton inelastic interactions will boost the accuracy of prompt gamma simulations. Among the built-in physics models, we found that the precompound model with a modified initial exciton state of 2 (1 particle, 1 hole) produced more accurate discrete gamma lines from the most important elements found within the body such as 16 O, 12 C and 14 N when comparing them with the available gamma production cross section data. Using the modified physics model, we investigated the prompt gamma spectra produced in a water phantom by a 200 MeV pencil beam of protons. The spectra were attained using a LaBr3 detector with a time-of-flight (TOF) window and BGO active shield to reduce the secondary neutron and gamma background. The simulations show that a 2 ns TOF window could reduce 99% of the secondary neutron flux hitting the detector. The results show that using both timing and active shielding can remove up to 85% of the background radiation which includes a 33% reduction by BGO subtraction.